Work-Related Well-Being Profiles among Health Education Teachers - Laitinen Satu (MDPI, 2022)
The aim of this cross-sectional study was to examine the well-being of Finnish health education teachers (n = 108) by examining the latent profiles of work burnout and work engagement by using a person-centered approach. Additionally, this study explored to what extent different job and personal resources (social support, pedagogical self-efficacy, and social belonging) and job demands (work overload) are associated with teachers' belonging to the work-related well-being profiles. The Job Demands-Resources model was used as the theoretical framework for this study. The study found that three different work-related well-being profiles could be identified among health education teachers: those who were engaged (45%), those who were already experiencing burnout (43%), and those at risk of burnout (12%). The more demands the teachers experienced, the likelier they were to belong to the burnout profile. Experiences of pedagogical self-efficacy, social belonging, and social support increased the probability of belonging to the engaged profile group. Determining job and personal resources and job demands might be beneficial for health education teacher well-being.